Bridging stakeholder perspectives to improve residential construction quality in growing urban environments - Iwko, Joanna; Dobrowolska, Anna; Klaus-Rosińska, Agata; Kuchta, Dorota; Pochybełko, Karol; Skorupka, Dariusz; Dudziak-Gajowiak, Dominika (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
This study aims to identify the most important quality factors in various phases of residential construction projects, as perceived by internal stakeholders – referred to in construction terminology as participants in the project implementation process – including construction engineers, site managers (construction site supervisors), contracting specialists, and company executives. To the authors’ knowledge, this is the first study to consider the individual perceptions of various residential construction project stakeholders and to explore the differences among them. Quality is understood as the absence of defects identified in the final acceptance process of the residential building, which constitutes the final product of the project. The research was based on questionnaires administered to 56 internal participants of eight residential construction projects. Respondents were asked to rate the importance of each of 33 proposed potential quality factors for attaining quality, as defined above. Most of the proposed factors were seen as significant by all or most project participant groups. However, several important differences among groups were identified. In some cases, they may be due to biases or emotions linked to the group’s direct involvement in a factor and implicit criticism. The implications of the findings, including the identified differences, for the management of individual phases of residential construction projects were outlined. Study limitations were acknowledged, and directions for future research were proposed.